EVALUATING THE CONTRIBUTION OF INTERNATIONAL TRADE TO ECONOMIC GROWTH IN SOUTH SULAWESI PROVINCE - Nurman (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2025)
This study aims to evaluate the contribution of international trade to the economic growth of South Sulawesi Province. As one of Indonesia’s emerging regional economies, South Sulawesi plays a strategic role in trade activities, both in exports and imports. Using a quantitative approach, the research employs time series data from 2010 to 2023 and applies multiple linear regression analysis to assess the relationship between trade indicators such as export value, import value, and trade balance and regional economic growth measured by Gross Regional Domestic Product (GRDP). The findings indicate that international trade, particularly exports, has a significant positive impact on regional economic performance. Conversely, import activities show a varied influence depending on the type and volume of goods traded. These results highlight the importance of strengthening export-oriented policies and improving trade infrastructure to sustain economic growth in South Sulawesi. The study contributes to regional development planning by offering empirical evidence on the trade-growth nexus at the sub-national level.